2019
DOI: 10.1136/bmjdrc-2019-000809
|View full text |Cite
|
Sign up to set email alerts
|

Improved well-being and decreased disease burden after 1-year use of flash glucose monitoring (FLARE-NL4)

Abstract: IntroductionThe FreeStyle Libre is a flash glucose monitoring (FSL-FGM) system. Compared with finger-prick based self-monitoring of blood glucose, FSL-FGM may provide benefits in terms of improved glycemic control and decreased disease burden.MethodsProspective nationwide registry. Participants with diabetes mellitus (DM) used the FSL-FGM system for a period of 12 months. End points included changes in HbA1c, hypoglycemia, health-related quality of life (12-Item Short Form Health Surveyv2 (SF-12v2) and 3-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 10 publications
5
81
1
2
Order By: Relevance
“…We have also found a significant reduction in diabetes‐related hospitalizations following the use of FCGM, consistent with previously published observational studies, 20,26 as well as a significant reduction in overall internal medicine hospitalizations. Patients purchasing FCGM technology probably experienced lower glycemic variability, as reflected by decreased hospitalization both for hyper‐ and hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
“…We have also found a significant reduction in diabetes‐related hospitalizations following the use of FCGM, consistent with previously published observational studies, 20,26 as well as a significant reduction in overall internal medicine hospitalizations. Patients purchasing FCGM technology probably experienced lower glycemic variability, as reflected by decreased hospitalization both for hyper‐ and hypoglycemia.…”
Section: Discussionsupporting
confidence: 92%
“…Worldwide, usage of continuous glucose monitoring and flash glucose monitoring is increasing 32 . Among users, improved treatment outcomes 33,34 and high treatment satisfaction are seen 35‐37 . However, adverse skin reactions to continuous glucose monitoring and/or insulin pumps have been reported as a persistent health issue affecting diabetes‐specific emotional distress among those affected 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed that flash glucose monitoring improved glycemic control, as assessed by HbA1c, compared with prior to its use (Table 2 ) [ 20 23 ]. In the Dutch prospective registry study, estimated HbA1c decreased from 8.0% before use of flash glucose monitoring to 7.6% after 6 months of use ( P < 0.001) and remained steady at 7.6% at 12 months ( P < 0.001).…”
Section: Real-world Observational Studies In Mixed Populations Of T1dmentioning
confidence: 99%